2010
DOI: 10.1175/2009jamc2131.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Town Energy Balance Model in Cold and Snowy Conditions during the Montreal Urban Snow Experiment 2005

Abstract: Using the Montreal Urban Snow Experiment (MUSE) 2005 database, surface radiation and energy exchanges are simulated in offline mode with the Town Energy Balance (TEB) and the Interactions between Soil, Biosphere, and Atmosphere (ISBA) parameterizations over a heavily populated residential area of Montreal, Quebec, Canada, during the winter-spring transition period (from March to April 2005). The comparison of simulations with flux measurements indicates that the system performs well when roads and alleys are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Modelling studies of cold cities are focused on a few sites mainly in North America (e.g. Valeo and Ho, 2004;Lemonsu et al, 2010;Leroyer et al, 2010) and Scandinavia (e.g. Semádeni-Davies et al, 1998).…”
Section: Järvi Et Al: Development Of Suews For Cold Climate Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling studies of cold cities are focused on a few sites mainly in North America (e.g. Valeo and Ho, 2004;Lemonsu et al, 2010;Leroyer et al, 2010) and Scandinavia (e.g. Semádeni-Davies et al, 1998).…”
Section: Järvi Et Al: Development Of Suews For Cold Climate Citiesmentioning
confidence: 99%
“…Similarly from the observations, the minimum (α min s ) and maximum (α max s ) snow albedo are set to 0.18 and 0.85, respectively, which differ from Le10 (α min n = 0.15-0.30 across the different surface cover types). In Lemonsu et al (2010) snow albedo aging time constants (τ f = 0.174, τ a = 0.008) could not be fully evaluated due to a lack of data. However, τ a compared to our observations is too small.…”
Section: Snow Propertiesmentioning
confidence: 99%
“…In order to estimate microclimate within street canyons, TEB is generally used in conjunction with the Surface Boundary Layer (SBL) model which solves vertical turbulent diffusion within the average street canyon from the surface fluxes provided by the road, wall and roof (Hamdi and Masson, 2008;Masson and Seity, 2009). Off-line simulations with TEB have already demonstrated that TEB was able to accurately reproduce the energy balance of urban surfaces, the street air temperatures and the energy consumptions for a wide range of cities under various climates and seasons: Vancouver and Mexico (Masson et al, 2002), Marseille (Lemonsu et al, 2004), Basel (Hamdi and Masson, 2008), Łódź (Offerle et al, 2005), Toulouse (Pigeon et al, 2008) and Montréal (Lemonsu et al, 2010). TEB simulates the thermal functioning of a generic building ( Figure 3): an energy balance is established on the outer surfaces of both wall and roof, taking into account the solar and infrared net radiation (Q*), the convective heat flux (Q H ), and the water evaporation (Q E ) for the roof.…”
Section: Surface Model Descriptionmentioning
confidence: 99%
“…The GEM model with the TEB parameterisation was tested for Oklahoma City (USA) with the resolution of 300 m against the dataset from the Joint Urban 2003 field experiment (Lemonsu et al, 2009). Also, the TEB parameterisation was tested for Montreal Urban Snow Experiment (MUSE) 2005, but as an off-line urban model (Lemonsu et al, 2010).…”
Section: Scenario Setup With the Teb Parameterizationmentioning
confidence: 99%